PENINGKATAN KETERAMPILAN PETERNAK AYAM PETELUR MELALUI SOSIALISASI MANAJEMEN BUDIDAYA DAN PELATIHAN PEMBUATAN PAKAN DARI BAHAN PAKAN LOKAL DI DESA TEGALSARI - Angriani, Ririn; Santosa, Purnama Edy; Hasiib, Etha Azizah; Febriyani, Widya; Ramadhani, Anisa; Alfiani, Zalfa; Hermawan, Heri; Ryan, Stefanus (Jurnal Media Tropika, 2025)
Improving farmers’ skills is one of the efforts to increase livestock productivity, which in turn will contribute to fulfilling the community’s need for animal protein and improving the economic conditions of the farmers. Kelompok Tani Ternak Berkah Jaya is a community partner in this flagship community service program located in Tegalsari Village, whose main livelihood is layer poultry farming. Based on a preliminary survey, Kelompok Tani Ternak Berkah Jaya is generally classified as a small-scale or traditional farm that still employs conventional poultry farming methods. Therefore, there is a need for outreach and training on modern layer chicken farming management. The outreach and training activities are expected to improve the farmers’ competencies in managing their poultry businesses. The implementation method of this flagship community service program consisted of three stages: (1) identifying the partner’s needs, (2) providing education on layer farming management and feed formulation training, and (3) conducting evaluations. The program was successfully carried out in Tegalsari Village. The evaluation results showed high enthusiasm from participants, particularly during the discussion sessions. Furthermore, survey results indicated an increase in participants’ knowledge of layer farming management, from 11.76% to 88.23%. The average hen-day production (HDP) over four weeks was 90.28%. Based on these results, it can be concluded that this flagship community service program successfully improved the farmers’ knowledge of layer chicken farming management, including aspects of maintenance, health, and feeding management